Dual role of p21 in regulating apoptosis and mitotic integrity in response to doxorubicin in colon cancer cells - Heeyeon Kim; Haein Kim; Eunjung Jang; Young-Woo Eom; Gyesoon Yoon; Kyeong Sook Choi; Eunhee Kim (Cell Death Discovery)
Abstract This study explores the multifaceted role of p21 in mediating cellular responses to DNA-damaging agents, with a focus on doxorubicin treatment in HCT116 colon carcinoma cells. We investigated how different doses of doxorubicin affect cells with varied p21 and p53 statuses, revealing distinct roles for p21 depending on the drug dosage. At high doses (HD), p21 is more critical than p53 in mediating apoptosis, whereas at low doses (LD), p21 is essential for preventing mitotic defects and multinucleation. Notably, reintroducing p21 or pharmacologically inhibiting CDK1 reduced multinucleation. The absence of p21 upon LD doxorubicin exposure led to aberrant chromosome segregation, persistent DNA damage response (DDR) activation, and increased non-homologous end-joining (NHEJ) activity, resulting in unrepaired DNA accumulation and multinucleation. Additionally, mitotic defects in p21-deficient cells were associated with mislocalization of key mitotic regulators, Aurora B and mitotic kinesin-like protein 1 (MKLP1), exacerbating defective mitosis. In summary, p21 functions as a dual regulator in response to DNA damage, promoting apoptosis at HD and preventing mitotic failure at LD. These insights have significant implications for cancer therapy, highlighting the potential of targeting the p21 to enhance treatment efficacy.